2022
DOI: 10.1002/jmri.28232
|View full text |Cite
|
Sign up to set email alerts
|

Directionally Sensitive Fractal Radiomics Compatible With Irregularly Shaped Magnetic Resonance Tumor Regions of Interest: Association With Osteosarcoma Chemoresistance

Abstract: BackgroundComputational analysis of routinely acquired MRI has potential to improve the tumor chemoresistance prediction and to provide decision support in precision medicine, which may extend patient survival. Most radiomic analytical methods are compatible only with rectangular regions of interest (ROIs) and irregular tumor shape is therefore an important limitation. Furthermore, the currently used analytical methods are not directionally sensitive.PurposeTo implement a tumor analysis that is directionally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In the previous review, the most frequently investigated question was whether radiomics could predict the NAC response [ 8 ], and it is still the most attractive topic nowadays in osteosarcoma radiomics [ 29 32 , 35 , 38 44 , 49 , 53 , 55 , 57 ]. The current review identified two studies each for differential diagnosis [ 37 , 54 ], for metastasis at diagnosis [ 46 , 47 ], and for early recurrence [ 33 , 34 ] of osteosarcoma, while none of the previous twelve studies touched upon these topics.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous review, the most frequently investigated question was whether radiomics could predict the NAC response [ 8 ], and it is still the most attractive topic nowadays in osteosarcoma radiomics [ 29 32 , 35 , 38 44 , 49 , 53 , 55 , 57 ]. The current review identified two studies each for differential diagnosis [ 37 , 54 ], for metastasis at diagnosis [ 46 , 47 ], and for early recurrence [ 33 , 34 ] of osteosarcoma, while none of the previous twelve studies touched upon these topics.…”
Section: Discussionmentioning
confidence: 99%
“…However, the outcome of such nonlinear dynamical systems can be investigated by their morphological characteristics with 2D images and/or 3D image volumes [ 9 , 10 ]. Interestingly, 1D morphological analysis is also highly relevant in oncology, mainly because of the full compatibility of 1D analysis with irregularly shaped tumour regions of interest (ROI) in medical images [ 11 ]. Another advantage of 1D analysis is its directional sensitivity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 1D morphological analysis is also highly relevant in oncology, mainly because of the full compatibility of 1D analysis with irregularly shaped tumour regions of interest (ROI) in medical images [ 11 ]. Another advantage of 1D analysis is its directional sensitivity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%